**Solving the Equation: 7(1-x)=10-6(x+2)**

In this article, we will solve the equation **7(1-x)=10-6(x+2)** step by step.

**Step 1: Expand the Left Side**

Let's start by expanding the left side of the equation:

**7(1-x) = 7 - 7x**

**Step 2: Expand the Right Side**

Now, let's expand the right side of the equation:

**10 - 6(x+2) = 10 - 6x - 12**

**Step 3: Simplify the Right Side**

Simplify the right side of the equation by combining like terms:

**10 - 6x - 12 = -2 - 6x**

**Step 4: Equate the Two Expressions**

Now, equate the two expressions:

**7 - 7x = -2 - 6x**

**Step 5: Solve for x**

To solve for x, add 7x to both sides of the equation:

**7 - 7x + 7x = -2 - 6x + 7x**

**7 = -2 + x**

Subtract 2 from both sides:

**9 = x**

Therefore, the value of **x** is **9**.

**Conclusion**

By following the steps above, we have successfully solved the equation **7(1-x)=10-6(x+2)** and found the value of **x** to be **9**.